Short Stature is Associated with Increased Risk of Dyslipidemia in Korean Adolescents and Adults - Oh, Na-Kyung; Song, Yun-Mi; Kim, Shin-Hye; Park, Mi Jung (Scientific reports, 2019)
Adults with short stature have been previously reported to have increased risk of cardiovascular events and hyper-LDL-cholesterolemia. We aimed to assess the association between height and lipid profiles among Korean adolescents and adults. We analyzed data from the Korea National Health and Nutrition Examination Survey from 2007 to 2015, from 37,889 individuals (aged 12–59 years). In adolescents, total cholesterol (TC) and low density lipoprotein-cholesterol (LDL-C) levels had profound associations with height in both boys and girls, while high density lipoprotein-cholesterol (HDL-C) levels had an inverse association with height only in boys. Height was inversely associated with TC, triglycerides (TG), and LDL-C concentrations in men and women and positively correlated with HDL-C concentration in women. In boys, the odds ratios (ORs) for hypercholesterolemia, hypertriglyceridemia, hyper-LDL-cholesterolemia were higher for shorter subjects (ORs = 2.38~7.01), while only the OR of hyper-LDL-cholesterolemia was significantly higher in girls with short stature (OR = 3.12). In adults, the ORs for hypercholesterolemia, hypo-HDL-cholesterolemia, and hyper-LDL-cholesterolemia were significantly higher in short subjects than in tall subjects after controlling for covariates (ORs = 1.50~2.61). Also, short men showed significantly higher ORs for hypertriglyceridemia (OR = 1.85) than tall men. Short stature was significantly associated with adverse lipid profiles in both adolescents and adults.